Pengaruh Social Media Advertising dan Event Marketing terhadap Brand Awareness dan Dampaknya pada Purchase Intention Produk Tenue de Attire - Rita Rita; Shania Febrine Nabilla (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The purpose of this study was to determine the relationship and influence between Social Media Advertising and Event Marketing on Brand Awareness and its impact on Tenue de Attire's Purchase Intention products. The population in this study were people who follow the official Tenue de Attire account on Instagram. This study uses Path Analysis to measure the relationship and the influence of independent variables with dependent variables. In this study, data was obtained by collecting questionnaires to the population through Direct Message. The results obtained in this study are, Social Media Advertising and Event Marketing have a significant influence on Brand Awareness and its impact on Tenue de Attire's Purchase Intention products.